Historic Preservation, Complexity, and the Shadow of Monumentality: The Case of Lutyens’ Delhi - Cem Kayatekin (ARCHive-SR)
Over the years, the central administrative district of New Delhi, known colloquially as Lutyens’ Delhi, dominantly shaped under the authorship of Sir Edwin Lutyens and Sir Herbert Baker, has been repeatedly called upon to support a wider range of uses and a higher range of densities than it currently houses. In reaction to such calls, arguments of historic preservation and conservation have been recycled in defense of the built environmental status quo within the area. One of the more layered arguments given for such a manner of preservation is that presented by Buch (2003) which pulls from a wide breadth of perspectives, ranging from basic arguments of architectural legacy to those which extrapolate connections between the Vastu Purusha and the masterplan inherent to Lutyens’ Delhi. This paper is framed as an intrinsic case study into the argument of Buch (2003), offering a detailed cross-examination, and by extension refutation, of the various historical and ideological assertions found therein.